Jouer à travailler. Idiome figuratif des groupes professionnels et figements narratifs du travail chez les figurines pour enfants - Michaël Meyer (Images du Travail, Travail des Images)
This article highlights how two major toy companies offer a combination of profane images of work and professional groups. In addition to increasing the readability of their products, the use of professional categories provides a set of evocative topics that are used to promote toys. The toys were studied from the angle of a social semiotics of representations. We draw the conclusion that the “mediagenie” of professions in toy figurines is used in a limited number of stereotypical narratives and representations of work. The article describes some principles of their structuration.